2021
DOI: 10.29309/tpmj/2021.28.04.4748
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Cobalamin deficiency in macrocytic anemia reporting at a Tertiary Care Hospital.

Abstract: Objective: Determine the frequency of vitamin cobalamin deficiency in macrocytic anemia cases reporting at tertiary care hospital. Study Design: Cross Sectional study. Setting: Faculty of Medicine and Allied Medical Sciences, Isra University, Hyderabad, Sindh Pakistan. Period: January 2017 to October 2018. Material & Methods: 450 cases of both genders, diagnosed as macrocytic- megaloblastic anemia were studied for the vitamin Cobalamin levels. Cases were collected through non- probability convenient sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…In distribution of women based on severity of low ferritin levels amongst 90 women, 41 (45.56%) women were observed with mild low ferritin levels, 43 (47.78%) women were observed with moderate low ferritin levels while 6 (6.66%) women were observed with severe low ferritin levels. In accordance with our study, another study carried out by NB Shaikh et al reported that mild, moderate and severe Low ferritin level in newborns were observed in 48.15%,45.37%, and 6.48% respectively 16 . Another study piloted by Shams et al reported that 43.5% of the newborns were in range of 12-30 ng/ml Serum ferritin levels 20 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In distribution of women based on severity of low ferritin levels amongst 90 women, 41 (45.56%) women were observed with mild low ferritin levels, 43 (47.78%) women were observed with moderate low ferritin levels while 6 (6.66%) women were observed with severe low ferritin levels. In accordance with our study, another study carried out by NB Shaikh et al reported that mild, moderate and severe Low ferritin level in newborns were observed in 48.15%,45.37%, and 6.48% respectively 16 . Another study piloted by Shams et al reported that 43.5% of the newborns were in range of 12-30 ng/ml Serum ferritin levels 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Based on hemoglobin level of participants with iron deficiency anemia, 52 (34.67%) women were observed with mild iron deficiency anemia, moderate iron deficiency anemia was observed in 87 (58%) women while 13 (8.67%) women were observed with severe iron deficiency anemia. In accordance with our study, another study carried out by NB Shaikh et al reported that mild, moderate and severe iron deficiency anemia amongst their study participants was observed in 31.52%, 61.41% and 7.07% women respectively 16 . Another study done by Qazi et al reported mild anemia in 52.5% participants, mild anemia in 27.5% and severe anemia in 19.9% which is consistent with our findings .…”
Section: Discussionsupporting
confidence: 92%
“…These findings were comparable to the previous some studies. [17,18] Most common symptoms were loss of weight, brittle nails, fast heartbeat, shortness of breath, fatigue and pale skin among all 210 patients. In the current study, the MCV for men was 97.6±5.32 fl vs. 107.5±11.08 fl for women (P=0.0001), indicating higher values.…”
Section: Ma Has a Well-established Cause: Dietary Vitamin Insufficiencymentioning
confidence: 99%